The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jphp.13222
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperuricemic and nephroprotective effects of extracts from Orthosiphon stamineus in hyperuricemic mice

Abstract: Objectives To investigate the antihyperuricemia and nephroprotective effects of Orthosiphon stamineus extracts on hyperuricemia (HUA) mice and explore the potential mechanisms. Methods Orthosiphon stamineus extracts were extracted using 50% ethanol and enriched using ethyl acetate, and characterised utilising UPLC/ESI‐MS. A potassium oxonate (PO) induced hyperuricemic mouse model was used to evaluate antihyperuricemia and nephroprotective effects of O. stamineus ethyl acetate extracts (OSE). Key findings Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This could further be correlated with the suppressed XO activity in these groups. Since XO activity is known to trigger inflammatory reactions and consequent tissue damage [ 22 ], the observed results further indicated the tissue protective potential of the triterpene.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This could further be correlated with the suppressed XO activity in these groups. Since XO activity is known to trigger inflammatory reactions and consequent tissue damage [ 22 ], the observed results further indicated the tissue protective potential of the triterpene.…”
Section: Discussionmentioning
confidence: 77%
“…Blood UA levels are physiologically regulated by XO activity, an enzyme that catalyzes the formation of UA from xanthine. The XO catalyzed reaction also generates reactive oxygen species (ROS) which can trigger inflammatory reactions and consequent tissue damage [ 22 ]. The reduced serum levels of UA along with decreased XO activity in the triterpene treated groups supported the antihyperuricemic effect of RA-3.…”
Section: Discussionmentioning
confidence: 99%
“…They further investigated the primary mechanisms that indicated O. aristatus probably increases the sensitivity of pancreatic beta cells to insulin or (and) peripheral utilization of glucose by the tissues for lowering plasma glucose [50,53]. Meanwhile, Chen and Xu et al [9,54] evaluated the function of anti-gout in mice. They showed that ethanolic and ethyl acetate fraction of O. aristatus possessed lowering serum uric acid (UA) and relieving pain because of the increasing excretion and the suppressing production of the UA, anti-inflammation, and analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Chen and Xu et al . (Xu et al, 2020; Chen et al, 2020) evaluated the function of anti-gout in mice. They showed that ethanolic and ethyl acetate fraction of O. aristatus possessed lowering serum uric acid (UA) and relieving pain because of the increasing excretion and the suppressing production of the UA, anti-inflammation, and analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation